Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Accès aux soins de longue durée dans la région d'Érié St. clair : Analyse et recommandation - Mian, Guy (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2021)
Ce rapport a été préparé dans le cadre du Plan d’Action Conjoint 2019-2022 du RLISS-Entité,¹ où les soins et les services aux aînés sont considérés comme prioritaires et, en particulier, l’accès aux soins de longue durée (SLD) dans la région d’Érié St. Clair. Le présent rapport vise à formuler des recommandations à l’intention de Santé Ontario (SO) Ouest afin de combler les lacunes en matière d’accessibilité aux soins de longue durée (SLD) en français et, par conséquent, dans les services de soutien à domicile et en milieu communautaires (SSDMC) afin de maintenir les aînés francophones à domicile dans la région d’Érié St. Clair (ESC). Dans la mesure du possible, le rapport proposera également des recommandations pour la localité de London dans la région du Sud-Ouest (S-O).

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., & Kubina, L.A. (2021, updated 2025). Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_innovative_practices.html fs-code-orig: Savard-2025b

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 10 : Les points de service satellites (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021d

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)